Wound dressing taking multi-component composite hydrogel as active component
Through the use of multi-component composite hydrogel, the problems of poor adhesion, breathability and wound damage in wound healing of traditional dressings are solved, and more efficient wound healing and wound repair effects are achieved.
Patent Information
- Application Number
- CN202510151265.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-25
AI Technical Summary
When treating skin wounds, existing traditional dressings have problems such as adhesion, lack of hemostasis, poor breathability and secondary damage to the wound, making it difficult to effectively promote the healing of specific wounds.
A wound dressing with a multi-component composite hydrogel as the active ingredient is used to form a three-dimensional network structure hydrogel through the combination of carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan, which has good breathability, water retention and angiogenic activity.
The dressing has greater potential in wound repair, can significantly increase wound healing speed, provide a suitable wet environment, enhance adhesion, and has self-healing and injectable capabilities, suitable for repair of irregular wounds.
Smart Images

Figure CN119868636A_ABST
Abstract
Description
[0001] This application is a divisional application based on the application No. 202411649521.X (the application date is 2024-11-19, and the invention name is a multi-component composite hydrogel, preparation method and application thereof). Technical Field
[0002] The invention relates to the technical field of biomaterials, in particular to a wound dressing with a multi-component composite hydrogel as an active ingredient. Background Art
[0003] Skin is the largest organ in the human body and is easily damaged by the external environment. Although it has a high potential for self-regeneration, severe skin defects heal slowly or do not heal spontaneously, which requires covering with skin substitutes. At present, the most widely used in clinical practice are traditional dressings, such as gauze, cotton balls, bandages, etc. These traditional dressings have certain hygroscopic and protective effects on the treatment of general wounds. Although gauze is low in cost and has good absorption capacity for exudate and can keep the wound dry, these traditional dressings are easy to adhere to the wound, lack hemostatic ability, have poor air permeability, and cause secondary damage to the wound surface, which is not conducive to the healing of specific wounds. Therefore, it is necessary to develop new medical dressings for the treatment of skin wounds.
[0004] In recent years, hydrogel has great potential in wound repair. Hydrogel is a three-dimensional network structure composed of physical or chemical cross-links of hydrophilic polymers. Among them, hydrogel is one of the candidates that can be used as dressings for different wounds due to its porous molecular structure, high water content, good biocompatibility and biodegradability. Summary of the invention
[0005] The present invention provides a wound dressing with a multi-component composite hydrogel as an active ingredient, which has a simple preparation process, low cost, is environmentally friendly and pollution-free, and has greater potential in wound repair.
[0006] A multi-component composite hydrogel comprises carboxymethyl yeast beta-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan.
[0007] The molecular weight of the carboxymethyl yeast β-1,3-glucan is 400-600 kD.
[0008] The substitution degree of the carboxymethyl yeast β-1,3-glucan is 50%-60%, and the angiogenesis-promoting activity is optimal within this range.
[0009] The carboxylation degree of the carboxymethyl chitosan is ≥80%. When the carboxylation degree of the carboxymethyl chitosan is lower than 80%, the solubility of the raw material and the subsequent gelling performance are affected.
[0010] The mass ratio of the carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan is 1:(1-3):(1-4). When the mass ratio exceeds this range, the gelling effect and gelling time of the multi-component composite hydrogel are affected.
[0011] When the multi-component composite hydrogel is stored at 25° C., a rheological test is performed within a stress range of 0.1 to 100%. When the angular frequency changes within a range of 0.1 to 100 rad / s, the storage modulus G' curve and the loss modulus G" curve intersect, wherein when the angular frequency changes from 0.1 to 4.6 rad / s, the loss modulus < storage modulus, and when the angular frequency changes from 4.6 to 100 rad / s, the loss modulus > storage modulus.
[0012] The amino groups of the carboxymethyl chitosan react with the aldehyde groups of oxidized carboxymethyl cellulose to form a hydrogel with a three-dimensional network structure, and the carboxyl groups of the carboxymethyl glucan and the amino groups of the carboxymethyl chitosan attract each other through charges to form ionic bonds. The carboxymethyl glucan is in a three-dimensional helical conformation and is attached to the hydrogel with a three-dimensional network structure, which can not only improve the biological function of the carboxymethyl yeast β-1,3-glucan, but also improve its mechanical properties.
[0013] The multi-component composite hydrogel has a gelling time of 6 to 12 minutes. If the gelling time is too short, it will gel in the syringe and cannot be injectable; if the gelling time is too long, it will gel slowly at the wound and cannot adhere to the wound surface in time.
[0014] A method for preparing a multi-component composite hydrogel, the specific steps comprising: (1) Preparation of carboxymethyl yeast β-1,3-glucan; (2) Preparation of oxidized carboxymethyl cellulose; (3) After the oxidized carboxymethyl cellulose and carboxymethyl yeast β-1,3-glucan are mixed and dissolved, the carboxymethyl chitosan aqueous solution is added and mixed to obtain a multi-component composite hydrogel; or, After carboxymethyl chitosan and carboxymethyl yeast β-1,3-glucan are mixed and dissolved, an oxidized carboxymethyl cellulose aqueous solution is added and mixed to obtain a multi-component composite hydrogel.
[0015] The carboxymethyl chitosan and oxidized carboxymethyl cellulose cannot be mixed before the carboxymethyl yeast β-1,3-glucan is added, otherwise, the carboxymethyl chitosan and oxidized carboxymethyl cellulose will gel, resulting in the inability to mix the yeast β-1,3-glucan.
[0016] Specifically, the method for preparing the multi-component composite hydrogel comprises: (1) Yeast β-1,3-glucan is added to isopropanol, and then sodium hydroxide aqueous solution is added, stirred for alkalization for 0.5 to 1.5 hours, monochloroacetic acid aqueous solution is added dropwise, and the temperature is raised to 50 to 70°C after the addition is completed, and the reaction solution is stirred for 1 to 4 hours to separate into layers, and the lower layer is taken out and poured into methanol, stirred for 0.5 to 1 hour, precipitated, and dried to obtain carboxymethyl yeast β-1,3-glucan sodium salt, and the obtained carboxymethyl yeast β-1,3-glucan sodium salt is dissolved in water, and after dissolution, hydrochloric acid aqueous solution is added to adjust the pH to 2 to 3, and poured into a mixed solvent, stirred for 10 to 30 minutes, filtered, washed with ethanol, and dried to obtain carboxymethyl yeast β-1,3-glucan; (2) adding carboxymethyl cellulose to a sodium periodate solution, stirring at 20-40° C. for 4-10 hours, filtering, and drying to obtain a crude product, adding the crude product to an ethylene glycol aqueous solution, stirring for 10-30 minutes, filtering, washing with deionized water, and drying to obtain oxidized carboxymethyl cellulose; (3) adding oxidized carboxymethyl cellulose to deionized water, adding carboxymethyl yeast β-1,3-glucan, dissolving, adding carboxymethyl chitosan aqueous solution, mixing, and standing for 10 to 30 minutes to obtain a multi-component composite hydrogel; or, Carboxymethyl chitosan was added into deionized water, carboxymethyl yeast β-1,3-glucan was added and dissolved, and oxidized carboxymethyl cellulose aqueous solution was added, mixed, and allowed to stand for 10 to 30 minutes to obtain a multi-component composite hydrogel.
[0017] In step (1), the mass ratio of the yeast β-1,3-glucan, isopropanol, sodium hydroxide aqueous solution and monochloroacetic acid aqueous solution is 1: (20-60): (0.3-0.8): (0.2-1).
[0018] Wherein, the concentration of the sodium hydroxide aqueous solution is 13-15 mol / L; The concentration of the monochloroacetic acid aqueous solution is 1-3 mol / L; The concentration of the hydrochloric acid aqueous solution is 1-3 mol / L.
[0019] The mixed solvent is a mixed solution of isopropanol and ethanol, and the mass ratio of isopropanol to ethanol is (2~1):1.
[0020] In step (2), the mass ratio of the carboxymethyl cellulose to the sodium periodate solution is 1:(4-20).
[0021] The sodium periodate solution is an aqueous solution of sodium periodate, wherein the mass ratio of sodium periodate to water is 1:(13-18).
[0022] In step (3), the mass ratio of the carboxymethyl yeast β-1,3-glucan to deionized water is 1:(15-30).
[0023] The mass concentration of the carboxymethyl chitosan aqueous solution is 4-6wt%; The mass concentration of the oxidized carboxymethyl cellulose aqueous solution is 4-6wt%.
[0024] The present invention also provides application of the multi-component composite hydrogel in wound dressings or wound repair materials.
[0025] The multi-component composite hydrogel has a DPPH free radical scavenging rate of not less than 40% and has excellent antioxidant capacity.
[0026] A wound dressing is characterized by using a multi-component composite hydrogel of carboxymethyl yeast beta-1,3-glucan as an active ingredient.
[0027] A wound repair material, characterized in that a multi-component composite hydrogel of carboxymethyl yeast β-1,3-glucan is used as an active ingredient.
[0028] Preferably, the wound dressing or wound repair material further comprises necessary auxiliary materials, including supporting materials, an absorption layer, and a protective film.
[0029] Yeast β-1,3-glucan contains β-(1→3)-linked straight chains and many β-(1→6)-linked branched structures. Due to its highly branched structure, it presents a three-dimensional helical conformation. This unique structure gives yeast β-1,3-glucan a variety of biological functions, including immunomodulation, anti-inflammation, and antioxidant functions, all of which have a positive effect on wound repair. However, the complex and highly branched structure of yeast β-1,3-glucan leads to its poor water solubility, which limits its application in wound healing. Carboxymethylation is an effective way to modify the structure of yeast β-1,3-glucan. After the introduction of carboxymethyl groups, its water solubility and biological activity are significantly improved.
[0030] Beneficial effects: 1. The present invention uses carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose, and carboxymethyl chitosan to prepare a multi-component composite hydrogel, wherein carboxymethyl yeast β-1,3-glucan has angiogenesis-promoting, immunomodulatory, and antioxidant effects; oxidized carboxymethyl cellulose and carboxymethyl chitosan are cross-linked into gel by Schiff base to obtain a three-dimensional network hydrogel structure, which not only has good air permeability and water retention effect, provides a suitable moist environment for wound healing, is conducive to wound healing, but also has self-healing and injectable capabilities, so that the multi-component composite hydrogel can be regenerated in situ and fill irregular wound areas. In addition, the carboxymethyl chitosan also has antibacterial activity and promotes wound healing.
[0031] 2. The present invention uses carboxymethyl yeast β-1,3-glucan as a raw material. Its spiral structure not only improves the wound healing ability of the multi-component composite hydrogel, but also cooperates with the hydrogel with a three-dimensional network structure to improve the mechanical properties of the multi-component composite hydrogel, so that it can deform when subjected to force and adapt to surfaces of different shapes, thereby improving its adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope image of the multi-component composite hydrogel prepared in Example 1; Figure 2 This is a self-healing image of the multi-component composite hydrogel prepared in Example 1; Figure 3 This is an image of the injectable properties of the multi-component composite hydrogel prepared in Example 1; Figure 4 This is a frequency scanning diagram of the multi-component composite hydrogel prepared in Example 1; Figure 5 This is a strain scanning diagram of the multi-component composite hydrogel prepared in Example 1; Figure 6 This is a continuous strain alternating scanning diagram of the multi-component composite hydrogel prepared in Example 1; Figure 7 This is an image of red blood cells treated with the multi-component composite hydrogel prepared in Example 1 in the hemolysis test; Figure 8 The DPPH free radical scavenging activity after treatment with the multi-component composite hydrogel prepared in Example 1; Fig. 9 The statistical results of the evaluation of L929 cell activity after incubation with the multi-component composite hydrogel extract prepared in Example 1 for 24h, 48h, and 72h; Fig.10 Migration images of L929 cells after incubation with the multi-component composite hydrogel extract prepared in Example 1 for 12 h, 24 h, and 48 h; Fig.11 Cell live / dead images after incubation in the multi-component composite hydrogel extract prepared in Example 1 for 24 h, 48 h, and 72 h; Fig.12 The multi-component composite hydrogel prepared in Example 1 promoted wound healing in diabetic mice. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described by the following examples. In the following implementation process, unless otherwise specified, the raw materials are all commercially available. Yeast β-1,3-glucan was purchased from Sigma-Aldrich, item number G5011.
[0034] Embodiment 1: The molecular weight of the carboxymethyl yeast β-1,3-glucan used in this example is 500 kD, and the degree of substitution is 55.1%; the degree of carboxylation of the carboxymethyl chitosan is greater than 80%.
[0035] A multi-component composite hydrogel, the preparation method is: (1) Preparation of carboxymethyl yeast β-1,3-glucan: 3 kg of yeast β-1,3-glucan was added to 60 kg of isopropanol, 1.2 kg of 14.3 mol / L sodium hydroxide aqueous solution was slowly added, and the mixture was stirred for alkalization for 1 hour. 2.5 kg of 2.1 mol / L monochloroacetic acid aqueous solution was added dropwise, and the temperature was raised to 60°C after the addition was completed. The reaction solution was stirred for 2 hours and then separated into layers. The lower layer was removed and poured into 300 kg of methanol. The mixture was stirred for 45 minutes to precipitate a solid, which was then dried to obtain carboxymethyl yeast β-1,3-glucan sodium salt. The obtained carboxymethyl yeast β-1,3-glucan sodium salt was dissolved in 30 kg of water, 2 mol / mL of hydrochloric acid aqueous solution was added to adjust the pH to 2.5, and the mixture was poured into a mixed solution of 200 kg of isopropanol and ethanol (the mass ratio of isopropanol to ethanol was 2:1), stirred for 30 minutes, and filtered. The solid was washed with 100 kg of ethanol and dried to obtain carboxymethyl yeast β-1,3-glucan. (2) 6 kg of carboxymethyl cellulose was placed in a brown conical flask, sodium periodate solution was added, stirred at 30 °C for 8 hours, filtered, and dried to obtain a white block crude product. The obtained crude product was added to 30 kg of ethylene glycol aqueous solution (0.1 mol / mL), stirred for 20 minutes, filtered, and the solid was washed with 100 kg of deionized water and dried to obtain oxidized carboxymethyl cellulose; (3) Take 1.5 kg of the oxidized carboxymethyl cellulose obtained in step (2) and add it to 30 kg of deionized water, add 1.5 kg of the carboxymethyl yeast β-1,3-glucan obtained in step (1), dissolve it by ultrasonication, add 40 kg of a 5% by mass carboxymethyl chitosan aqueous solution, mix, and let stand for 20 minutes to obtain a multi-component composite hydrogel.
[0036] The sodium periodate solution is prepared as follows: 6.4 kg of sodium periodate is taken, and 100 kg of deionized water is added to dissolve the mixture to obtain a sodium periodate solution.
[0037] Embodiment 2: This embodiment is the same as embodiment 1, except that step (3) is: 1.5 kg of carboxymethyl chitosan was added to 30 kg of deionized water, and 1.5 kg of carboxymethyl yeast β-1,3-glucan obtained in step (1) was added and dissolved by ultrasonication. 40 kg of 5% by mass oxidized carboxymethyl cellulose aqueous solution was added, mixed, and allowed to stand for 20 minutes to obtain a multi-component composite hydrogel.
[0038] Comparative Example 1: This comparative example is the same as Example 1, except that the mass ratio of the carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan is 1:3:0.5.
[0039] Comparative Example 2: This comparative example is the same as Example 1, except that carboxymethyl yeast β-1,3-glucan is not added in this comparative example.
[0040] Test example: (1) Gelation time test The inversion no-backflow observation method was used. 2 mL of the hydrogels prepared in Examples 1-2 and Comparative Example 1 were placed in a glass bottle with a rubber stopper. Timing was started from the time of pouring, and observation was made every 1 minute until the inversion no-backflow phenomenon occurred. The results are shown in Table 1.
[0041] Table 1 Gelation time test results
[0042] It can be seen from the results in Table 1 that the multi-component composite hydrogels prepared in Example 1 and Example 2 have a relatively fast gelation time, which is conducive to rapid gelation at the wound, acting as a protective barrier and helping the wound to heal.
[0043] (2) Microscopic morphological characteristics The freeze-dried multi-component composite hydrogel was subjected to gold spraying treatment, and the microscopic morphology of the multi-component composite hydrogel prepared in Example 1 was observed by scanning electron microscopy (Quattro S). Figure 1 As shown. Figure 1 It can be seen from the results that the multi-component composite hydrogel presents a three-dimensional porous morphology with relatively uniform distribution.
[0044] (3) Self-healing characteristics test The self-healing ability is important for hydrogel dressings because it can fill the wound area and withstand external mechanical forces and extend the service life of the hydrogel. The self-healing performance of the multi-component composite hydrogel prepared in Example 1 was evaluated by direct visual method. Two pieces of red and blue multi-component composite hydrogels were placed together at room temperature without any external intervention and their self-healing behavior was observed within 1 hour. The results are shown in Figure 2. Figure 2 As shown, two pieces of multi-component composite hydrogels can reform into a complete cylindrical hydrogel without external force, which proves that the multi-component composite hydrogel prepared in Example 1 has good self-healing properties.
[0045] (4) Injectability test Continuously squeeze out through a 5mL syringe to draw the letters "XCH". The result is as follows Figure 3 As shown, the injectability and wound shape adaptability of the multi-component composite hydrogel prepared in Example 1 were confirmed.
[0046] (5) Rheological properties test The hydrogel was placed on a rheometer, the temperature was set at 37°C, the strain was 1%, and the frequency of the multi-component composite hydrogel prepared in Example 1 was scanned. Different angular frequencies were applied with a change of 0.1-100 rad / s, and the storage modulus (G′) and loss modulus (G″) were analyzed. The results are as follows: Figure 4 shown. Figure 4 It can be seen from the results that the storage modulus (G′) of the multi-component composite hydrogel prepared in Example 1 exceeds the loss modulus (G″), which means that the multi-component composite hydrogel has a gel-like behavior.
[0047] The temperature was set at 25°C, and amplitude scanning was performed. By changing the stress range γ = 0.1-100%, the critical strain point of the multi-component composite hydrogel was detected, and the changes of G′ and G″ of the multi-component composite hydrogel with strain were investigated. The results are shown in Figure 5 shown. Figure 5 It can be seen from the results that the intersection between G′ and G″ of the multi-component composite hydrogel is 4.6%, indicating that the network of the multi-component composite hydrogel obtained in Example 1 is destroyed.
[0048] The temperature was set at 25°C and the frequency was 1 Hz. The strain was alternately scanned. First, the strain was set to 1% and the time scan test was performed for 60 s. Then, the strain was set to 800% and the time scan was performed for 25 s. The test was repeated for 5 cycles to investigate the changes in G′ and G″ of the multi-component composite hydrogel prepared in Example 1. The results are shown in FIG. Figure 6 shown. Figure 6 It can be seen from the results that after five rheological cycles, G′ and G″ also returned to their original values, proving that the multi-component composite hydrogel has good self-healing ability and a relatively stable structure. When the strain is 800%, the decrease in G′ indicates that the network of the multi-component composite hydrogel obtained in Example 1 is destroyed.
[0049] (6) In vitro hemolysis test 1 mL of rabbit anticoagulated whole blood was slowly added into 10 mL of PBS. The red blood cells were suspended by pipetting and centrifuged at 1000 r / min for 7 min. The supernatant was slowly aspirated and discarded. 10 mL of PBS was added and the centrifugation was repeated 3 times until the supernatant was colorless and transparent. The red blood cells precipitated for the last time were collected and recorded as 100 wt%. A red blood cell diluent with a concentration of 4 wt% was prepared with PBS for later use.
[0050] The multi-component composite hydrogel prepared in Example 1 was added to deionized water to prepare 500 μg / mL, 1 mg / mL, 1.5 mg / mL, and 2 mg / mL multi-component composite hydrogel suspensions, 500 μL of 4 wt% red blood cell diluent was added thereto, respectively, and the suspensions were kept in a constant temperature water bath at 37°C for 1 hour, and the suspensions were taken out and centrifuged at a speed of 1000 r / min for 10 minutes as the sample group. PBS was used as the blank group and Triton X-100 with a mass concentration of 1% was used as the control group. The results are shown in FIG. Figure 7 shown.
[0051] Figure 7 It can be seen from the results that the supernatants of the multi-component composite hydrogels with concentrations of 500 μg / mL, 1 mg / mL, 1.5 mg / mL, and 2 mg / mL are almost completely transparent, indicating that the multi-component composite hydrogel prepared in Example 1 has a low hemolysis rate. The supernatant was taken in a 96-well plate, and the absorbance measured at 540 nm by an ELISA instrument was less than 5%, which once again proved that the multi-component composite hydrogel prepared in Example 1 has a low hemolysis rate.
[0052] (7) DPPH free radical scavenging experiment The antioxidant properties of the multi-component composite hydrogel were determined by DPPH free radical scavenging experiment. The specific steps are as follows: a. The multi-component composite hydrogel prepared in Example 1 after freeze-drying was dissolved in 75 wt % methanol, and methanol solutions of the multi-component composite hydrogel with concentrations of 500 μg / mL, 1 mg / mL, 1.5 mg / mL, and 2 mg / mL were prepared as sample groups, 1 mL of the sample group solution was taken, added to 1 mL of DPPH methanol solution (0.2 mM), incubated in the dark for 30 min, and the absorbance A was measured at 517 nm. 样 .
[0053] b. Take 1 mL of the methanol solution containing the multi-component composite hydrogel and 1 mL of a mixture of 75 wt% methanol as the blank group, and measure the absorbance A according to the method in step a. 空 .
[0054] c. Take a mixture of 1 mL DPPH methanol solution (0.2 mM) and 1 mL 75 wt% methanol solution as the control group, and measure the absorbance A according to the method in step a. 对 .
[0055] d. Calculate the DPPH clearance rate according to the following formula: .
[0056] The results are as follows Figure 8 As shown, Figure 8It can be seen from the results that the multi-component composite hydrogel prepared in Example 1 has a good scavenging effect on DPPH, proving that it has good antioxidant properties.
[0057] (8) Cytotoxicity test a. L929 cells were cultured with MEM medium containing fetal bovine serum and double antibodies. L929 cells were inoculated into a 96-well plate with a cell density of 5000 cells / well. After the cells adhered to the wall, the culture medium was removed and the sample group extract was added. The cells were cultured for 24 h, 48 h, and 72 h, respectively. CCK-8 was added and the absorbance OD1 was measured at 450 nm with a microplate reader after incubation for 1 h.
[0058] Preparation of the sample group extract: Weigh 100 mg of the multi-component composite hydrogel obtained in Example 1, add it to a centrifuge tube, add 10 ml of MEM, incubate at 37° C. for 24 hours, centrifuge, and filter with a microporous filter membrane to obtain multi-component composite hydrogel extracts with concentrations of 50 μg / mL, 200 μg / mL, and 800 μg / mL.
[0059] b. Use a cell-free control group as the blank control group, and measure the absorbance OD0 according to the method in step a; use cells incubated with no hydrogel as the cell control group, and measure the absorbance OD2 according to the method in step a.
[0060] c. Calculate cell viability using the following formula: .
[0061] Among them, OD1 is the absorbance value of the sample group, OD2 is the absorbance value of the cell control group, and OD0 is the absorbance value of the blank control group. The calculation results are as follows Fig. 9 As shown, the blank group is the cell viability of the cell control group. Fig. 9 It can be seen from the results that after L929 cells were incubated with the MEM culture medium containing the multi-component composite hydrogel prepared in Example 1, the cell survival rate was very high, proving that the multi-component composite hydrogel prepared in Example 1 was non-toxic to L929 cells.
[0062] (9) Cell scratch test L929 cells were seeded in a 6-well plate at a cell density of 500,000 cells / well and cultured in MEM medium containing fetal bovine serum and double antibodies. After the cells adhered to the wall, 3 lines were drawn in each well with a 200 μL pipette tip, and the extracts of the multi-component composite hydrogel prepared in Example 1 with concentrations of 50 μg / mL, 200 μg / mL, and 800 μg / mL were added respectively. The cells were incubated for 12 h, 24 h, and 48 h, and photographed under a microscope. The results are shown in FIG. Fig.10 As shown, the blank group did not add the multi-component composite hydrogel extract. Fig.10 It can be seen from the results that as the concentration of the multi-component composite hydrogel prepared in Example 1 increases, the migration ability of L929 cells becomes stronger, and the scratches in the high-concentration group are basically closed, which confirms that the multi-component composite hydrogel prepared in Example 1 is beneficial to the migration of fibroblasts in the wound as a wound dressing.
[0063] (10) Cell live / dead staining test L929 cells were seeded in a 96-well plate at a cell density of 5000 cells / well. After the cells adhered to the wall, the culture medium was removed, and the extracts of the multi-component composite hydrogel prepared in Example 1 with concentrations of 50 μg / mL, 200 μg / mL, and 800 μg / mL were added, respectively, and incubated for 24 h, 48 h, and 72 h, respectively. The live / dead cells were fluorescently stained using a Calcein AM / PI cell activity detection kit, and incubated at 37°C in the dark for 30 min. Photos were taken using a fluorescent inverted microscope, and the live cells were stained with Calcein AM reagent, and the dead cells were stained with PI reagent. The results are as follows: Fig.11 As shown. Fig.11 It can be seen from the results that after L929 cells were incubated with the MEM culture medium containing the multi-component composite hydrogel prepared in Example 1, the cell survival rate was very high and the number of dead cells was small. As the incubation time increased, the cell proliferation increased.
[0064] (11) Promote wound healing in diabetic mice Six-week-old C57BL / 6J male mice (weighing about 25g) were fasted for 4 hours and intraperitoneally injected with streptozotocin at a dose of 5mg / 100g for 5 consecutive days. One week after the injection, the fasting blood glucose levels of the mice were measured, and 18 mice with blood glucose levels greater than 16.6mmol / L were randomly divided into a model group, a two-component drug group, and a three-component drug group, with 6 mice in each group. All mice were anesthetized with chloral hydrate, the hair on the back of the mice was shaved, and a wound with a diameter of about 1 cm was made on the back with a punch. The wound in the model group was not treated in any way, and the two-component drug group and the three-component drug group were covered with the hydrogels prepared in Example 2 and Example 1 with a diameter of 1 cm and a thickness of 3 mm, respectively. All mice were photographed on the 0th, 6th, and 18th days of feeding to observe the healing of the back wounds. The results are as follows Fig.12 As shown, after the mouse wound was treated with the multi-component composite hydrogel prepared in Example 1, the healing speed was significantly accelerated. On the 18th day, the wound was almost completely healed, proving that the multi-component composite hydrogel prepared in the present invention can significantly promote the healing of the wound surface of diabetic mice.
Claims
1. A wound dressing with a multi-component composite hydrogel as an active ingredient, characterized in that: The multi-component composite hydrogel is used as the active ingredient and also includes auxiliary materials; The multi-component composite hydrogel consists of carboxymethyl yeast beta-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan.
2. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 1, characterized in that: The mass ratio of the carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan is 1:(1-3):(1-4).
3. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 1, characterized in that: The degree of substitution of the carboxymethyl yeast β-1,3-glucan is 50%-60%.
4. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 1, characterized in that: The molecular weight of the carboxymethyl yeast β-1,3-glucan is 400-600 kD.
5. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 1, characterized in that: The carboxylation degree of the carboxymethyl chitosan is ≥80%; The gelling time of the multi-component composite hydrogel is 6 to 12 minutes.
6. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 1, characterized in that: The auxiliary materials include supporting materials, an imbibition layer and a protective film.
7. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 1, characterized in that: The preparation steps of the multi-component composite hydrogel include: (1) Preparation of carboxymethyl yeast β-1,3-glucan; (2) Preparation of oxidized carboxymethyl cellulose; (3) After the oxidized carboxymethyl cellulose and carboxymethyl yeast β-1,3-glucan are mixed and dissolved, the carboxymethyl chitosan aqueous solution is added and mixed to obtain a multi-component composite hydrogel; or, After carboxymethyl chitosan and carboxymethyl yeast β-1,3-glucan are mixed and dissolved, an oxidized carboxymethyl cellulose aqueous solution is added and mixed to obtain a multi-component composite hydrogel.
8. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 7, characterized in that: The preparation steps of the multi-component composite hydrogel include: (1) Yeast β-1,3-glucan is added to isopropanol, and then sodium hydroxide aqueous solution is added, stirred for alkalization for 0.5 to 1.5 hours, monochloroacetic acid aqueous solution is added dropwise, and the temperature is raised to 50 to 70°C after the addition is completed. The reaction solution is stirred for 1 to 4 hours to separate into layers, and the lower layer is taken out and poured into methanol, stirred for 0.5 to 1 hour, precipitated, and dried to obtain carboxymethyl yeast β-1,3-glucan sodium salt. The obtained carboxymethyl yeast β-1,3-glucan sodium salt is dissolved in water, and after dissolution, hydrochloric acid aqueous solution is added to adjust the pH to 2 to 3, and then poured into a mixed solvent, stirred for 10 to 30 minutes, filtered, washed with ethanol, and dried to obtain carboxymethyl yeast β-1,3-glucan; (2) adding carboxymethyl cellulose to a sodium periodate solution, stirring at 20-40° C. for 4-10 hours, filtering, and drying to obtain a crude product, adding the crude product to an ethylene glycol aqueous solution, stirring for 10-30 minutes, filtering, washing with deionized water, and drying to obtain oxidized carboxymethyl cellulose; (3) adding oxidized carboxymethyl cellulose to deionized water, adding carboxymethyl yeast β-1,3-glucan, dissolving, adding carboxymethyl chitosan aqueous solution, mixing, and standing for 10 to 30 minutes to obtain a multi-component composite hydrogel; or, Carboxymethyl chitosan was added into deionized water, carboxymethyl yeast β-1,3-glucan was added and dissolved, and oxidized carboxymethyl cellulose aqueous solution was added, mixed, and allowed to stand for 10 to 30 minutes to obtain a multi-component composite hydrogel.
9. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 8, characterized in that: In step (1), the mixed solvent is a mixed solution of isopropanol and ethanol; In step (2), the sodium periodate solution is an aqueous solution of sodium periodate.
10. The wound dressing with a multi-component composite hydrogel as an active ingredient according to claim 1, characterized in that: The DPPH free radical scavenging rate of the multi-component composite hydrogel is not less than 40%.